Factors Aﬀecting Customer Loyalty of Islamic Bank in Sumbawa City, Indonesia - Rizka Alwathan; Peni Nugraheni (IAIN Salatiga, 2021)
This study aims to examine the factors aﬀecting customer loyalty in Sumbawa city, Nusa Tenggara Barat province, Indonesia. This province become the driving factor of the Islamic bank market because it is dominated by 97% Muslims. Meanwhile, the independent factors include proﬁt sharing, service quality, transparency, and trust. Data were collected using a questionnaire and analyzed using multiple regression methods. The results showed that service quality, transparency, and trust positively aﬀect the customer loyalty of Islamic bank, while proﬁt sharing have no inﬂuence. Furthermore, Muslim ﬁnancial institutions are expected to use their best performance to increase customer loyalty. The practitioners and regulators can improve their performance and develop the Islamic ﬁnancial industry by considering the result above.